Effect of smoking on serum lipid profile amongst stroke patients: A descriptive study from Dhaka, Bangladesh - Habib, Nasrin; Rashid, Mamunur; Afzal, Farzana; Roy, Bedanta; Afrose, Tahmina (Journal of Biomedical Sciences, 2018)
Background Stroke causes death and disability, has an emotional and economic impact on patients, families, and society. The present study was undertaken to compare the serum lipids levels in adult male smokers and non-smoker stroke patients. Material and methods The participants were selected from indoor medicine units of Dhaka Medical College and Hospital, Dhaka, Bangladesh. A total number of 105 stroke patients age >20 years were selected, of whom, 30 were non-smokers and 75 were smokers. Results TC, TG, LDL-C is significantly higher in the smoker stroke patients comparing non-smokers. Serum HDL is significantly higher in non-smokers. Conclusion Serum lipid profile is altered in smokers, which increases the risk of stroke and other cardiovascular disorders, so intense awareness program about adverse health events of smoking should be considered by all means including the social media campaign and implementation of its importance to the curriculum. Journal of Biomedical Sciences. 2017;4(2):11-15